Basin morphology, sedimentology and seismic stratigraphy of an upland lake from Serra dos Carajás, southeastern Amazon, Brazil - Souza-Filho, Pedro Walfir M.; Guimarães, José Tasso F.; Silva, Marcio S.; Costa, Francisco R.; Sahoo, Prafulla K.; Maurity, Clovis W.; Dall’Agnol, Roberto (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
To understand the sedimentary processes in a lake environment, it is essential to investigate the morphological, sedimentalogical and limnological features of the basin. The present study was developed at Violão Lake, Serra Sul de Carajás. The methodological approach comprises the collection of bathymetric and sedimentary data, and shallow seismic profiles. Lake Violão has a NE-SW elongated guitar-shaped form and ~0.3 km2 of surface area, with a perimeter of ~2.7 km. The lake presents washing basin morphology and it is marked by a steep margin carved in duricrust outcrops, while the bottom is flat and constituted mainly by muddy sediments. The water column is stratified only during the dry season and it is mixed in the rainy season. Three seismic stratigraphic successions were identified in the lake resting on prominent basal reflector (bedrock), which reaches a maximum depth of ~15 m. Small lobate masses are deposited in the bottom of the lake from underflows, while the central part of the lake is characterized by drape deposition, suggesting that organic-mud sedimentation is associated to pelagic deposition from dilute interflows or overflows. Therefore, the sedimentary processes are strongly regulated by basin morphology, drainage water inflow and thermal stratification of the water column.
Keywords: Upland lake; Sedimentology; Lacustrine sedimentary facies; Amazon